2019
DOI: 10.1016/j.isci.2019.10.053
|View full text |Cite
|
Sign up to set email alerts
|

A Read/Write Mechanism Connects p300 Bromodomain Function to H2A.Z Acetylation

Abstract: HIGHLIGHTS p300 acetylates H2A.Z at multiple N-terminal lysine residues Interaction of p300 bromodomain with H4ac enhances H2A.Zac H2A.Zac and H4ac colocalize at active regulatory regions H4ac and H2A.Zac differential signature can define the enhancer state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Interestingly, a significant portion of this acetylation occurs as diacetylation and triacetylation of K4, K7, and K11. TIP60 [68,84], p300 [73], and KAT2A [85], in the context of DNA repair, can acetylate H2A.Z in cells. Bromodomain proteins bind to acetylated lysines and in vitro studies showed that the bromodomain PHD finger transcription factor (BPTF) interacts with K7ac on H2A.Z.2, while the bromodomain of CECR2 preferentially binds H2A.Z.1ac [142]; however, further in vivo validation will be necessary to confirm this interaction.…”
Section: Glossarymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a significant portion of this acetylation occurs as diacetylation and triacetylation of K4, K7, and K11. TIP60 [68,84], p300 [73], and KAT2A [85], in the context of DNA repair, can acetylate H2A.Z in cells. Bromodomain proteins bind to acetylated lysines and in vitro studies showed that the bromodomain PHD finger transcription factor (BPTF) interacts with K7ac on H2A.Z.2, while the bromodomain of CECR2 preferentially binds H2A.Z.1ac [142]; however, further in vivo validation will be necessary to confirm this interaction.…”
Section: Glossarymentioning
confidence: 99%
“…Interestingly, various studies have found that active intragenic enhancers in expressed genes are depleted of H2A.Z or H2A.Zac [73,74], which could be due to active removal of H2A.Z at gene bodies during transcription elongation [75,76]. Notably H2A.Z-marked active enhancers may not be present within the gene they activate, as transcription elongation of the gene would remove H2A.Z from the enhancer, suggesting that H2A.Z enhancers may likely be acting as trans-regulatory elements.…”
Section: Trends Trends In In Genetics Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, differential acetylation of the two isoforms could alter their different functional outcome. For instance, the flexibility of the n-terminal tail between different isoforms can be enhanced by their specific acetylation, regardless of the lack of difference observed in the acetylation rate of H2A.Z-1 and H2A.Z-2 by p300 [95]. Also, it has been shown that H2A.Z-2 preferentially associates with H3K4me3 [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed a novel dipyrene analogue, Pyr-A, and used it to probe biomolecule condensates formed by LLPS. These include in vitro droplets formed by intrinsically disordered regions (IDRs) of bromodomain-containing protein 4 (BRD4) ( Caputo et al., 2021 ; Colino-Sanguino et al., 2019 ; Sabari et al., 2018 ), and centrosomes, which are dynamic and spherical membraneless intracellular organelles ( Tiwary and Zheng, 2019 ) ( Figure 1 B). Centrosomes are surrounded by pericentriolar material (PCM) ( Andersen et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%